Relationship of Predisposing Factor (Knowledge, Attitude And Demography) and Reinforcing Factor (Husband Support and Health Personnel) To The Precision of The Progestinal Prospective KB Review Time in Poly PKBRS Kabupaten Hospital Aceh Tamiang In 2018 - Tarigan, Ria Sepriza Br (Sari Mutiara Indonesia University Press, 2018)
The increase in population is a global problem throughout the world. Handling it can be done by making KB (Family Planning) program. Some information reveals that injection is most popularly used as a modern contraceptive device. A wrong use of KB injection can cause acceptors to get pregnant. It is usually because they are late in reuse it. A study showed that 60% to 78% of women get pregnant one year after they use the last injection. The research used a survey method with cross sectional design. It was done at the Poliklinik KB of the Regional General Hospital of Aceh Tamiang Regency. The pollution was 80 acceptors of progestin injection, and all of them were used as the samples (total sampling). The data were analyzed by using simple regression analysis. The result of the research showed that predisposing factors (knowledge, education, occupation, and distance) and reinforcing factors (husbands’ support) had the influence on punctuality in revisiting progestin injection. Of the five variable, husbands’ support had the most dominant influence on the punctuality in revisiting progestin injection at the Poliklinik KB of the Regional General Hospital of Aceh Tamiang Regency (OR=8.594). Revisiting acceptors who were not punctual were OR=85% and punctual were 15%. It is recommended that injection contraceptive devise be used as it is more effective ad husbands support their wives to use it and accompany them in revisiting progestin injection so that the health care providers can give complete information about the benefit and the side-effect of progestin injection contraception and can increase husbands’ understanding about progestin injection.